2012
DOI: 10.1186/1742-4755-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific, evidence-based planning for scale-up of family planning services to increase progress to MDG 5: health systems research

Abstract: BackgroundUnmet need for family planning is responsible for 7.4 million disability-adjusted life years and 30% of the maternity-related disease burden. An estimated 35% of births are unintended and some 200 million couples state a desire to delay pregnancy or cease fertility but are not using contraception. Unmet need is higher among the poorest, lesser educated, rural residents and women under 19 years. The barriers to, and successful strategies for, satisfying all demand for modern contraceptives are heavily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…27 Specific emphasis must be directed to women under 25 years of age who are more likely to request premature discontinuation of their IUDs and may benefit from additional counselling. 28 (Byrne et al, 2012 andMostafa Kamal, 2012) 29,30 added that women with the lowest education level and poorest quintile were least likely to use any contraception method. The lack of knowledge about contraceptives was rarely cited as a reason for non-use.…”
Section: Discussionmentioning
confidence: 99%
“…27 Specific emphasis must be directed to women under 25 years of age who are more likely to request premature discontinuation of their IUDs and may benefit from additional counselling. 28 (Byrne et al, 2012 andMostafa Kamal, 2012) 29,30 added that women with the lowest education level and poorest quintile were least likely to use any contraception method. The lack of knowledge about contraceptives was rarely cited as a reason for non-use.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its importance, the health information systems of the four countries included in the study entirely overlook service quality in their composition of indicators. Our study revealed that the quality of government family planning services was a major factor limiting utilisation in Indonesia, Nepal, the Philippines (Byrne et al 2012) and India. Complications from incorrect insertion of intrauterine devices, poor counselling for appropriate methods and mismanagement of side effects were frequently reported (Aldaba et al 2011;Morgan et al 2011;Trisnantoro et al 2011;Varghese et al 2011Varghese et al , 2012.…”
Section: No Data Available On Determinants Nor Quality Of Servicementioning
confidence: 80%
“…Several studies have explored the effects of internal migration on various health issues (Abas et al 2009;Ebrahim et al 2010;Lu 2010), and our study revealed that temporary migration, for both work and cultural purposes, can also have a large effect on requirements for family planning service delivery and effective use of methods. For example, in Nepal, significant male migration for work means that different sexual and reproductive needs exist for the short time in which men return home and for those periods when they are separated (Morgan et al 2011).…”
Section: Limited Understanding Of How Temporary Migration Patterns Afmentioning
confidence: 81%
See 1 more Smart Citation
“…Methods of strengthening may include expanding the capacity of the organisation and staff to implement a programme -a critical factor in success of scale up [5]. Running a specific programme within a broader group of health services [53] may in some instances result in a more efficient use of existing resources.…”
Section: Health-systems Strengtheningmentioning
confidence: 99%